Experimental study of the process of welding of pipe bills under vibration impact - Балакин, Валерий; Кадильникова, Татьяна; Савкин, Святослав; Кадильникова, Анастасия (SWorldJournal, 2021)
The article proposes an effective way to reduce the residual stresses arising in the welded seams of pipes, based on the use of vibration in the welding process. The experimental study was divided into the following stages: welding of longitudinal preform